2019
DOI: 10.1074/jbc.ra118.006298
|View full text |Cite
|
Sign up to set email alerts
|

Two alternative mechanisms regulate the onset of chaperone-mediated assembly of the proteasomal ATPases

Abstract: The proteasome holoenzyme is a molecular machine that degrades most proteins in eukaryotes. In the holoenzyme, its heterohexameric ATPase injects protein substrates into the proteolytic core particle, where degradation occurs. The heterohexameric ATPase, referred to as 'Rpt ring', assembles through six ATPase subunits (Rpt1-Rpt6) individually binding to specific chaperones (Rpn14, Nas6, Nas2, and Hsm3). Here, our findings suggest that the onset of Rpt ring assembly can be regulated by two alternative mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 61 publications
(113 reference statements)
1
23
0
Order By: Relevance
“…The main control point is through regulated expression of the corresponding suite of proteasome subunits and associated genes, which is tightly co-ordinated in an attempt to provide stoichiometric amounts of each polypeptide (Figure 2). How tight this regulation is within the collection of proteasome genes remains unclear, as excess subunits do not typically accumulate within cells as free forms (the exception being Rpn10), and appear to be rapidly degraded if they fail to integrate into their respective CP or RP sub-complexes (Peters et al, 2015; Nahar et al, 2019). Thus, while transcription and translation are modulated in an attempt to provide stoichiometric expression, an important arbiter dictating the final concentration of proteasomes might be the abundance of one or more factors in limiting supply.…”
Section: Transcriptional Regulation Of 26s Proteasome Subunit Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…The main control point is through regulated expression of the corresponding suite of proteasome subunits and associated genes, which is tightly co-ordinated in an attempt to provide stoichiometric amounts of each polypeptide (Figure 2). How tight this regulation is within the collection of proteasome genes remains unclear, as excess subunits do not typically accumulate within cells as free forms (the exception being Rpn10), and appear to be rapidly degraded if they fail to integrate into their respective CP or RP sub-complexes (Peters et al, 2015; Nahar et al, 2019). Thus, while transcription and translation are modulated in an attempt to provide stoichiometric expression, an important arbiter dictating the final concentration of proteasomes might be the abundance of one or more factors in limiting supply.…”
Section: Transcriptional Regulation Of 26s Proteasome Subunit Abundancementioning
confidence: 99%
“…A second pathway is the removal of non-functional proteasome subunits by the UPS itself prior to their integration into the holo-proteasome. Hsp42 was shown to be important in yeast by coalescing these polypeptides into cytoplasmic condensates from which they are cleared by active 26S proteasomes (Peters et al, 2015; Nahar et al, 2019).…”
Section: Autophagy-mediated Control Of 26s Proteasome Abundancementioning
confidence: 99%
“…The second pathway is by the breakdown of dysfunctional proteasome subunits by the UPS itself to avoid their misassembly into the proteasome holoenzyme. It was shown that yeast Hsp42 coalesces the dysfunctional subunits into cytoplasmic condensates that can be removed by the proteasome itself (Peters et al 2015;Nahar et al 2019). The third pathway is by proteaphagy that relies on the autophagy system, which degrades large heterogeneous cytoplasmic constituents, such as organelles, protein aggregates and invasive pathogens Marshall et al 2016;.…”
Section: Autophagic Control Of Proteasomementioning
confidence: 99%
“…Efforts by several labs in recent years have revealed a surprising complexity in the localization of proteasomes under different stress conditions in a number of organisms 9,19,20,24,25,37,38 . Monitoring the dynamic nature of proteasome assembly, proteasome autophagy, and PSG formation has relied on fluorescent tags fused to particular subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This is because there is some functional redundancy within the proteasome, and regulatory mechanisms exists that compensate for reduced proteasome activity by upregulating proteasome levels. For instance, when the proteasome assembly chaperones Hsm3 or Nas2 are deleted individually, cells typically grow at rates similar to wild type 5 , 8 , 9 . However, yeast harboring deletions of both chaperones are very sensitive to heat and other protein folding stresses.…”
Section: Introductionmentioning
confidence: 99%